Declining malaria transmission differentially impacts the maintenance of humoral immunity to Plasmodium falciparum in children - Mugyenyi, CK; Elliott, SR; Yap, XZ; Feng, G; Boeuf, P; Fegan, G; Osier, FFH; Fowkes, FJI; Avril, M; Williams, TH; Marsh, K; Beeson, JG (Oxford University Press, 2017)
Background We investigated the poorly understood impact of declining malaria transmission on maintenance of antibodies to Plasmodium falciparum merozoite antigens and infected erythrocytes (IEs), including functional immunity.